الأبنیة التي استوی فیها اللزوم و التعدي فی كتاب دستور اللغة للنظنزي (ت 497 هـ) تحقیق و دراسة - أغا, طه صالح أمین (Sulaimani Journal for Humanities, 2025)
This study tries to achieving the manuscript which is about Arabic Linguistics and belongs to the Iranian Scholar “Abu Abdulla Husein Al Natanzy Al asfahani(497 Hijri). The title of the manuscript is “ The Structures in which Intransitives are equal to Transitives “. It is a chapter of the book Known as “ Dustur Al lugha”:it means: the rule of the language. The title seeks to shed light on the features of some verbs in Arabic Language, which are intransitive and transitive in the same time. The scholar (syntactian) listed160 verbs and more in the same manner of dictionaries giving the meaning of the verbs along with sentential examples for each verb. This syntactic work is regarded as an outstanding work in the field. “ Dustur Al lugha” is an old manuscript Up to this moment, it has been achieved and studied thoroughly. The researcher selects and studies only one chapter of the manuscript to enrich the Arabic Library and to encourage the Arabic readers and researchers to achieving the whole manuscript. Using the scientific method to achieving the manuscript. The study starts with an Introduction which includes a suitable study about this manuscript along with a couple of pages of the copy of the original manuscript.